METHODOLOGICAL AND DIDACTIC ASPECTS OF ONLINE LANGUAGE LABS (International journal of artificial intelligence, 2026)
The article explores the pedagogical foundations and instructional principles underlying the use of online language laboratories in foreign language education. The study focuses on methodological approaches and didactic strategies that support effective language learning in digital environments. It examines how online language labs facilitate skill integration, learner autonomy, differentiated instruction, and formative assessment. Special attention is given to the alignment of online language labs with modern teaching methodologies such as communicative language teaching, task-based learning, and constructivist pedagogy. The article argues that the success of online language labs depends not only on technological tools but also on sound methodological and didactic design.